Incidence of penile neoplasia associated with the use of pesticides in the Irrigated Perimeter Jaguaribe Apodi - Ceará, Brazil: An in silico approach (Research, Society and Development, 2022)
The insertion of irrigated perimeters and the intensive use of pesticides made the Baixo Jaguaribe region one of the most critical areas of agribusiness in Ceará. However, the excessive use of pesticides has been associated with increased cases of premature births, congenital malformations and mainly neoplasms, especially penile cancer. Objective: To characterize in silico the pesticides of the triazine group used in the Jaguaribe-Apodi Irrigated Perimeter in the Baixo Jaguaribe region to investigate the relationship between penile cancer associated with the use of pesticides. Methodology: It was given through molecular modeling using Classical Force Field (MMF94) to obtain more stable structures and physicochemical properties and molecular docking to elucidate the possible inhibition between ligand (triazine)-protein (p53). Results:  The electronic and structural characterization established that the pesticides of the triazine group are soluble and have no rotation, their double bonds are derived from the heterocyclic ring in their conformations and the stability energies are relatively high. Conclusions: Regarding molecular docking, ametryn and atrazine are likely to initiate a carcinogenic response to workers in the Jaguaribe-Apodi Irrigated Perimeter, i.e., penile cancer, while cyromazine ligand shows no interactions with p53 protein; thus, it does not act with inhibitory potency.